Effects of the breed and the live weight on the fatty acid and amino acid content, and the biological value of the proteins of the Hungarian Simmental’s and Holstein-Friesian’s meat - Holló, Gabriella; Csapó, János; Tőzsér, János; Holló, István; Szűcs, Endre (Acta Agraria Kaposváriensis, 2000)
21 Hungarian Simmental and 17 Holstein-Friesian cattle’s meat has been analysed in regard to the fatty acid and amino acid content, and also to the biological value of the protein. It was established that the proportion of the saturated, and the mono- and polyunsaturated fatty acids compared to each other is not significantly influenced by the breed and the live weight. By the increase of the live weight, examining both breed, the ratio of the monounsaturated fatty acids has increased in the meat. The amino acid content of the meat was not significantly influenced by the breed, and the live weight did not produce any demonstrated effects, either. The essential amino acid content and the biological value of the meat of the Hungarian Simmental are practically the same as of the Holstein-Friesian.
Keywords: Meat composition; Hungarian Simmental; Holstein-Friesian amino acid composition; biological value